2015
DOI: 10.1080/21645515.2015.1046659
|View full text |Cite
|
Sign up to set email alerts
|

Addition of CpG ODN and Poly (I:C) to a standard maturation cocktail generates monocyte-derived dendritic cells and induces a potent Th1 polarization with migratory capacity

Abstract: Monocyte-derived dendritic cells (DCs) are used as immunoadjuvant cells in cancer vaccines and have made great progress. However, an optimal DCs subset is vital for this treatment effect, the current 'gold standard' cytokine cocktail DCs have a shortcoming in their cytokines secretion, especially IL-12p70, mainly because of the existence of PGE2. Therefore, it is necessary to find an appropriate DCs-based immunotherapeutic protocol. In this study, we compared a novel 'improved' maturation cytokine cocktail wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…For instance, Rizzo et al 28 reported that pretreatment with low-molecular-weight hyaluronan during the preparation of DC vaccines enhanced the migratory capacity of DCs through increasing the expression of CCR7. Zhu et al 29 showed that the addition of CpG ODN and Poly (I: C) to the maturation cocktail could generate DC vaccines with higher migratory potential. In the present study, our results showed that exposure to LDR during the preparation of DC vaccines also promoted the migration of DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Rizzo et al 28 reported that pretreatment with low-molecular-weight hyaluronan during the preparation of DC vaccines enhanced the migratory capacity of DCs through increasing the expression of CCR7. Zhu et al 29 showed that the addition of CpG ODN and Poly (I: C) to the maturation cocktail could generate DC vaccines with higher migratory potential. In the present study, our results showed that exposure to LDR during the preparation of DC vaccines also promoted the migration of DCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the production of IL-12 by a DC vaccine generated by conventional methods was still insufficient, which was considered to be responsible for, at least in part, the unsatisfying clinical outcomes of using DC vaccines for cancer immunotherapy. 29,38 Dendritic cell vaccines with an increased ability to produce IL-12 have been proven to prime stronger CTLs in vitro and result in greater tumor growth inhibition in vivo. 38,39 However, the authors did not report whether the administration of such a DC vaccine could result in a further increase in serum IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…DCs’ generation was performed as previously described by Zhu et al[ 25 ]. A concentrated leukocyte fraction was isolated from PBMCs that processed 200 mL of blood during each collection.…”
Section: Methodsmentioning
confidence: 99%
“…Maturation cocktails and other immunoadjuvants can be used to promote the immunostimulatory activity of exogenously activated DCs [6][7][8] . The nature of immunoadjuvants determines the type, the magnitude, the breadth, and the quality of antitumor immune response 9 .…”
mentioning
confidence: 99%